2011
DOI: 10.1007/s00134-011-2131-6
|View full text |Cite
|
Sign up to set email alerts
|

Donor conversion rates depend on the assessment tools used in the evaluation of potential organ donors

Abstract: PurposeIt is desirable to identify a potential organ donor (POD) as early as possible to achieve a donor conversion rate (DCR) as high as possible which is defined as the actual number of organ donors divided by the number of patients who are regarded as a potential organ donor. The DCR is calculated with different assessment tools to identify a POD. Obviously, with different assessment tools, one may calculate different DCRs, which make comparison difficult. Our aim was to determine which assessment tool can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…All current proposed definitions of imminent BD are based on the loss of brainstem reflexes [17,18]. Of the set of brainstem reflexes tested upon admission, we found that the abolition of corneal reflexes was most predictive of BD, and that its predictive value did not differ according to whether the ICH was infratentorial.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…All current proposed definitions of imminent BD are based on the loss of brainstem reflexes [17,18]. Of the set of brainstem reflexes tested upon admission, we found that the abolition of corneal reflexes was most predictive of BD, and that its predictive value did not differ according to whether the ICH was infratentorial.…”
Section: Discussionmentioning
confidence: 74%
“…Zurasky et al [10] found that patients with ICH who evolved to BD had a lower median admission Glasgow Coma Scale score (without defining a threshold), and that AfricanAmerican patients evolved more often to BD and were less concerned by early decisions to withdraw life support. Some experts have recently proposed definitions of imminent BD based on abolished brain stem responses [17,18]. Recently, analyzing patients who died on an ICU in Dutch university hospitals, it has been reported that 45.6% of patients with imminent BD actually evolved toward BD [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1) [5]. In a retrospective chart analysis, IBD proved to be the most practical tool to identify patients with a realistic chance to become brain dead, and therefore to identify patients most likely to become organ donors [6]. It is essential that all researchers use the same definition for potential organ donor recognition.…”
mentioning
confidence: 99%